Antidiabetic Effects of Quercetin and Silk Sericin in Attenuating Dysregulation of Hepatic Gluconeogenesis in Diabetic Rats Through Potential Modulation of PI3K/Akt/FOXO1 Signaling: In Vivo and In Silico Studies - Heba M. Abdou; Ghada M. Abd Elmageed; Hussein K. Hussein; Imane Yamari; Samir Chtita; Lamia M. El-Samad; Mohamed A. Hassan (Journal of Xenobiotics)
Type 2 diabetes mellitus (T2DM) is an intricate disease correlated with many metabolic deregulations, including disordered glucose metabolism, oxidative stress, inflammation, and cellular apoptosis due to hepatic gluconeogenesis aberrations. However, there is no radical therapy to inhibit hepatic gluconeogenesis disturbances yet. We thus sought to probe the effectiveness and uncover the potential mechanism of quercetin (QCT) and silk sericin (SS) in mitigating hyperglycemia-induced hepatic gluconeogenesis disorder, which remains obscure. Administration of QCT and SS to diabetic male albino rats markedly restored the levels of glucose, insulin, advanced glycation end-products (AGEs), liver function enzymes, alpha-fetoprotein (AFP), globulin, and glycogen, in addition to hepatic carbohydrate metabolizing enzymes and gluconeogenesis in comparison with diabetic rats. Furthermore, treatment with QCT and SS modulated hepatic malondialdehyde (MD), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), nitric oxide, tumor necrosis factor-alpha (TNF-α), and interleukin-1β (IL-1β), in addition to serum interleukin-6 (IL-6) and cyclooxygenase-2 (COX-2), implying their effectiveness in safeguarding cells against oxidative impairment and inflammation. Remarkably, QCT and SS treatments led to the upregulation of expression of phosphatidylinositol 3-kinases (PI3K), phospho-Akt (p-Akt), and forkhead box-O1 (FOXO1) genes in hepatic tissues compared to diabetic rats, orchestrating these singling pathways for curtailing hyperglycemia and pernicious consequences in hepatic tissues. Importantly, immunohistochemical investigations exhibited downregulation of caspase-3 expression in rats treated with QCT and SS compared to diabetic animals. Beyond that, the histopathological results of hepatic tissues demonstrated notable correlations with biochemical findings. Interestingly, the in silico results supported the in vivo findings, showing notable binding affinities of QCT and SS to PI3K, GPx, and TNF-α proteins. These results imply that QCT and SS could mitigate oxidative stress and inflammation and regulate hepatic gluconeogenesis in diabetic rats. However, QCT revealed greater molecular interactions with the studied proteins than SS. Overall, our results emphasize that QCT and SS have significant therapeutic effects on attenuating hyperglycemia-induced hepatic gluconeogenesis, with QCT showing superior effectiveness.